A Circular Mentoring sebagai Model Evaluatif Regeneratif untuk Pengembangan UMKM melalui Simulasi Kuantitatif dan Indikator Kesiapan - Raliby, Oesman; Nisa Ulinuha, Faisa (Borobudur Engineering Review, 2025)
Conventional mentoring models in the development of Micro, Small, and Medium Enterprises (MSMEs) often fail to capture the regenerative dynamics within small business communities. This study develops the Circular Mentoring approach as a data-driven evaluative model that enables systematic role transitions between mentees and mentors. Using quantitative simulations based on four main variables—Responsibility of Supervision (Rs), Response to Development (Rd), Business Development Score (ST), and Transition Readiness Function (T(r))—this study analyzed data from 120 MSME actors from three cities and regencies in Java. The simulation results indicate that the ST score has a positive correlation (r = 0.72) with role transition readiness, while T(r) exhibits a logistic distribution, suggesting a threshold for role regeneration at a T(r) value of≥ 0.65. Based on these findings, the Circular Mentoring Performance Tool (SMPT) was developed, an evaluative dashboard that integrates additional indicators such as the Impact Score, Mentor Retention Rate, and Role Regeneration Index. This model provides an evidence-based approach for MSME facilitators to design more adaptive, inclusive, and sustainable mentoring strategies. Keywords: MSMEs; Circular Mentoring; Regenerative Evaluation; Quantitative Simulation